2008
DOI: 10.1002/app.28819
|View full text |Cite
|
Sign up to set email alerts
|

Poly(butylene terephthalate)/clay nanocomposite compatibilized with poly(ethylene‐co‐glycidyl methacrylate). I. Isothermal crystallization

Abstract: Poly(butylene terephthalate) (PBT)/clay nanocomposite was prepared by blending PBT and commercial modified montmorillonite clays via a extruder by using poly(ethylene-co-glycidyl methacrylate) (PEGMA) as a compatibilizer (PBT/PEGMA/Clay). PEGMA and clay were also blended with PBT to prepare PBT/PEGMA and PBT/Clay, respectively. The morphology was investigated by wide-angle X-ray diffraction (WAXD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The clays were aggregated togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
2
17
0
1
Order By: Relevance
“…PEGMA can chemically react with PBT and increase the viscosity to reduce molecular mobility and crystallization in PBT/PEGMA (Huang, 2008a). The exfoliated silicates provided a large number of nucleation centers to enhance crystallization in PBT/PEGMA/clay nanocomposites.…”
Section: Compatibility and Interfacial Propertiesmentioning
confidence: 99%
“…PEGMA can chemically react with PBT and increase the viscosity to reduce molecular mobility and crystallization in PBT/PEGMA (Huang, 2008a). The exfoliated silicates provided a large number of nucleation centers to enhance crystallization in PBT/PEGMA/clay nanocomposites.…”
Section: Compatibility and Interfacial Propertiesmentioning
confidence: 99%
“…In a recent report, Huang suggested that the clay layers were exfoliated in the PBT matrix in the presence of compatibilizer, and this resulted in an enhanced nucleation of PBT [46,47] .…”
Section: Polybutylene Terephthalate (Pbt)mentioning
confidence: 99%
“…They are reported to be the materials of 21st century, possessing unique property combinations that are not found in conventional composites [1,2]. Several researchers have studied polymer-clay nanocomposites based on poly(butylene terephthalate) (PBT) [1][2][3][4][5]. Impact modification of engineering thermoplastic polymers, especially polyesters and polyamides, has received considerable attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Impact modification of engineering thermoplastic polymers, especially polyesters and polyamides, has received considerable attention in recent years. In this category, PBT is of significant importance because of its unique combination of properties, such as rigidity, solvent resistance, good thermal stability, good chemical resistance, and rate of crystallization and it is widely used in various applications such as electronics and engineering materials [3][4][5]. In order to obtain the desired properties, PBT has been blended with many polymers or inorganic nanoparticles, which imparts the required properties for many applications [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%